Using the PATROL model to evaluate the performance of banks in Algeria Case study of Gulf Bank Algeria during the period 2015-2022 - reguigberra, hemza; zeid, Aymen (Journal of Research in Finance and Accounting, 2025)
The study aims to know how to use the PATROL model in evaluating the performance of banks by applying this model to Algerian Gulf Bank AGB during the period (2015–2022). The evaluation included the elements that make up the PATROL model, which are mainly represented in: capital adequacy, profitability, liquidity, credit risk, and organization. The results of the study concluded that Gulf Bank Algeria was classified in Class No. 2, meaning that the bank’s performance is "satisfactory." The results also showed that the PATROL model explains some weak points in performance that require periodic and continuous monitoring by those in charge of Gulf Bank Algeria to correct them in a timely manner. Before it gets worse, it is appropriate.